Šolc-Type Wavelength Filters Based on TE↔TM Mode Conversion Utilizing Periodically Poled Ti-Diffused Lithium Niobate Channel Waveguides - Hongsik Jung (International Journal of Optics)
We have demonstrated the Šolc-type wavelength filters in a 52 mm long periodically poled Ti-diffused lithium niobate channel waveguide which has a domain period of 16.6 μm. At room temperature, the center wavelength and the full-width at half maximum of the filter were about 1272.49 nm and 0.23 nm, respectively. The nearest side-lobe is about 7 dB. New structure of optical add/drop multiplexer (OADM) utilizing Šolc-type TE↔TM mode converters was proposed for the first time.